Country report: Pharmacy education and practice in the context of Mongolia - Dorj, G.; Sunderland, B.; Sanjjav, T.; Gendenragchaa, B.; Dorj, G.; Hendrie, Delia; Parsons, R. (International Pharmaceutical Federation, 2018)
With the decentralisation of the Soviet Union system, Mongolia has gone through many challenges. The pharmaceutical sector has been privatised and over 80% of drugs are imported with Mongolia largely depending on international sources. Pharmacy education was traditionally orientated towards industry and product formulation. Most pharmacy graduates would seek positions in pharmaceutical marketing or industry. This has resulted in a shortage of pharmacists in other sectors. Pharmacy education has been acknowledged to be one of the important issues to be addressed in Mongolia. In order to improve the quality of the education and keep up with international standards, including Japan and the United States of America, the pharmacy curriculum has been revised seven times. A recent revision of the curriculum now includes clinical pharmacy and pharmacy practice. However, little information has been published describing pharmacy education in Mongolia. The information presented in this report may create discussion and critical analysis and planning, and it is hoped to be useful for further modification of pharmacy programmes to achieve desired educational outcomes.